Pharmaceutical and biomedical applications of capillary electrophoresis - Lunte, S. M. (Susan M.); Radzik, D. M. (Donna M.); ScienceDirect eBooks (Oxford, OX, U.K. ; Tarrytown, N.Y., U.S.A. : Pergamon, 1996)
The book describes the theory and applications of Capillary Electrophoresis (CE) in the field of pharmaceutical and biomedical analysis. It is targeted towards users who are intimately involved in analytical problems, especially those which involve small samples. This book presents the technique of capillary electrophoresis from the point of view of the serious hands-on use in the field of pharmaceutical and biomedical analysis. An overview of general theory is presented to acquaint the novice with the fundamental principles. A more theoretical approach is taken in the presentation of electrokinetic chromatography. The next chapter discusses advances in column technologies, the preceding chapters having provided a foundation as to how separations occur. In the next three chapters, recognized experts in their fields present fundamentals and state-of-the-art techniques in the areas of optical, electrochemical and mass spectrometric detection. The major focus of the remaining chapters is on applications. This includes the analysis of pharmaceuticals, amino acids and peptides, macromolecules, nucleosides, nucleotides and oligonucleotides. The use of CE for analysis of small ions and separation of biological particles is also discussed. The issue of sample preparation for analysis by CE is addressed, especially as it relates to clinical analysis.
Section headings and papers: List of Contributors. Introduction. Separations. Principles and theory of capillary electrophoresis (S.M. Lunte, D.M. Radzik). Column technologies for capillary electrophoresis (J.K. Towns, F.E. Regnier). Electrokinetic chromatography (J.P. Foley, E.S. Ahuja). Detection. Optical detection strategies in capillary electrophoresis (S.A. Soper). Capillary electrophoresis/mass spectrometry (R.D. Smith, H.R. Udseth). Electrochemical detection for capillary electrophoresis (T.J. O'Shea). Applications. Sample preparations for capillary electrophoresis (D.K. Lloyd). Capillary electrophoresis in the study of amino acids (P.L. Weber). Capillary electrophoresis of peptides and proteins (K.L. Kostel). Separation of nucleic acids and oligonucleotides and sequencing of DNA fragments by capillary electrophoresis (R.P. Singhal, Jun Xian). The use of capillary electrophoresis in pharmaceutical development (Sou Chan Chang et al.). Capillary electrophoresis-based methods for in vivo analysis: single cell analysis and microdialysis sampling (B.L. Hogan). Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Elsevier
Keywords: Capillary electrophoresis; Biomolecules -- Analysis; Drugs -- Analysis; Electrophoresis, Capillary -- methods; MEDICAL -- Drug Guides; MEDICAL -- Pharmacology; MEDICAL -- Pharmacy; MEDICAL -- Nursing -- Pharmacology; Biomolecules -- Analysis; Capillary electrophoresis; Drugs -- Analysis; Biologische Medizin; Kapillarelektrophorese; Pharmazie; Electronic books